Adherence to healthy lifestyle and risk of gestational diabetes mellitus: prospective cohort study. (30th September 2014) - Zhang, Cuilin; Tobias, Deirdre K; Chavarro, Jorge E; Bao, Wei; Wang, Dong; Ley, Sylvia H; Hu, Frank B
Abstract : Objective To quantify the association between a combination of healthy lifestyle factors before pregnancy (healthy body weight, healthy diet, regular exercise, and not smoking) and the risk of gestational diabetes. Design Prospective cohort study. Setting Nurses' Health Study II, United States. Participants 20 136 singleton live births in 14 437 women without chronic disease. Main outcome measure Self reported incident gestational diabetes diagnosed by a physician, validated by medical records in a previous study. Results Incident first time gestational diabetes was reported in 823 pregnancies. Each lifestyle factor measured was independently and significantly associated with risk of gestational diabetes. The combination of three low risk factors (non-smoker, ≥150 minutes a week of moderate to vigorous physical activity, and healthy eating (top two fifths of Alternate Healthy Eating Index-2010 adherence score)) was associated with a 41% lower risk of gestational diabetes compared with all other pregnancies (relative risk 0.59, 95% confidence interval 0.48 to 0.71). Addition of body mass index (BMI) <25 before pregnancy (giving a combination of four low risk factors) was associated with a 52% lower risk of gestational diabetes compared with all other pregnancies (relative risk 0.48, 0.38 to 0.61). Compared with pregnancies in women who did not meet any of the low risk lifestyle factors, those meeting all four criteria had an 83% lower risk of gestational diabetes (relative risk 0.17, 0.12 to 0.25). The population attributable risk percentage of the four risk factors in combination (smoking, inactivity, overweight, and poor diet) was 47.5% (95% confidence interval 35.6% to 56.6%). A similar population attributable risk percentage (49.2%) was observed when the distributions of the four low risk factors from the US National Health and Nutrition Examination Survey (2007-10) data were applied to the calculation. Conclusions Adherence to a low risk lifestyle before pregnancy is associated with a low risk of gestational diabetes and could be an effective strategy for the prevention of gestational diabetes.